Biodegradation of phenol and benzene by endophytic bacterial strains isolated from refinery wastewater-fed Cannabis sativa. Issue 13 (3rd July 2018) - Iqbal, Aneela; Arshad, Muhammad; Hashmi, Imran; Karthikeyan, Raghupathy; Gentry, Terry J.; Schwab, Arthur Paul
ABSTRACT: The presence of benzene and phenol in the environment can lead to serious health effects in humans and warrant development of efficient cleanup strategies. The aim of the present work was to assess the potential of indigenous endophytic bacterial strains to degrade benzene and phenol. Seven strains were successfully isolated from Cannabis sativa plants irrigated with oil refinery wastewater. Molecular characterization was performed by 16S rRNA gene sequencing. Phenol was biodegraded almost completely with Achromobacter sp. (AIEB-7), Pseudomonas sp. (AIEB-4), and Alcaligenes sp. (AIEB-6) at 250, 500, and 750 mg L −1 ; however, the degradation was only 81%, 72%, and 69%, respectively, when exposed to 1000 mg L −1 . Bacillus sp. (AIEB-1), Enterobacter sp. (AIEB-3), and Acinetobacter sp. (AIEB-2) degraded benzene significantly at 250, 500, and 750 mg L −1 . However, these strains showed 80%, 72%, and 68% benzene removal at 1000 mg L −1 exposure, respectively. Rates of degradation could be modeled with first-order kinetics with rate constant values of 1.86 × 10 −2 for Pseudomonas sp. (AIEB-4) and 1.80 × 10 −2  h −1 for Bacillus sp. (AIEB-1) and half-lives of 1.5 and 1.6 days, respectively. These results establish a foundation for further testing of the phytoremediation of hydrocarbon-contaminated soils in the presence of these endophytic bacteria.